1996
DOI: 10.1016/s0092-8674(00)81372-0
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Grb2 from the Met Receptor In Vivo Reveals Complex Roles in Muscle Development

Abstract: Hepatocyte growth factor (HGF) and its receptor, the Met tyrosine kinase, are determinants of placenta, liver, and muscle development. Here, we show that Met function in vivo requires signaling via two carboxy-terminal tyrosines. Mutation of both residues in the mouse genome caused embryonal death, with placenta, liver, and limb muscle defects, mimicking the phenotype of met null mutants. In contrast, disrupting the consensus for Grb2 binding allowed development to proceed to term without affecting placenta an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
261
2
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 294 publications
(276 citation statements)
references
References 37 publications
11
261
2
2
Order By: Relevance
“…Accordingly, the constitutively active oncogenic counterpart of the Met receptor (Tpr ± Met) transforms ®broblasts at high e ciency, and renders them highly metastatic (Park et al, 1986;Giordano et al, 1997). Met signaling and transformation depend on ligand-induced phosphorylation of two carboxy-terminal docking sites of mixed speci®city (Y 1349 /VHVNATY 1356 /VNV, Ponzetto et al, 1994;Fixman et al, 1995;Maina et al, 1996). These phosphotyrosines are responsible for recruiting a number of SH2-containing e ectors, including p85 (the regulatory subunit of PI 3-kinase) and the Grb2 adaptor (Ponzetto et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the constitutively active oncogenic counterpart of the Met receptor (Tpr ± Met) transforms ®broblasts at high e ciency, and renders them highly metastatic (Park et al, 1986;Giordano et al, 1997). Met signaling and transformation depend on ligand-induced phosphorylation of two carboxy-terminal docking sites of mixed speci®city (Y 1349 /VHVNATY 1356 /VNV, Ponzetto et al, 1994;Fixman et al, 1995;Maina et al, 1996). These phosphotyrosines are responsible for recruiting a number of SH2-containing e ectors, including p85 (the regulatory subunit of PI 3-kinase) and the Grb2 adaptor (Ponzetto et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These tyrosine residues are part of a consensus sequence (YVH/NV) which mediates coupling of the receptor with several e ectors, including the Grb2/SoS complex (Ponzetto et al, 1994;Fixman et al, 1995), the p85 regulatory subunit of PI-3-kinase (Ponzetto et al, 1993), Stat-3 (Boccaccio et al, 1998), and the multiadaptor protein Gab1 (Weidner et al, 1996;Bardelli et al, 1997b;Nguyen et al, 1997). Grb2, in particular, requires an Asn in the +2 position for binding, and is thus linked to the receptor via the Y 1356 VNV motif Maina et al, 1996;Fixman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A number of observations suggest that c-met is a downstream target of pax3, already clearly implicated in human alveolar RMS. As in pax3-de®cient Splotch mice, myogenic precursor cells in c-met-de®cient mice cannot populate the limbs, and limb and diaphragm muscles fail to develop (Bober et al, 1994;Goulding et al, 1994;Bladt et al, 1995;Maina et al, 1996). Expression of c-met in lateral dermomyotome is downregulated in Splotch mice (Daston et al, 1996;Epstein et al, 1996;Yang et al, 1996), although c-metindependent muscular anomalies have been described in this mutant as well (Dietrich et al, 1999).…”
Section: The Patched/pax/met Connectionmentioning
confidence: 99%
“…Skeletal muscle progenitor cells that form limb, tongue, and diaphragm musculature delaminate from the epithelial dermomyotome of the somites by an epithelial-to-mesenchymal transition and migrate to their final destination where they complete differentiation (Christ and Brand-Saberi, 2002). Loss of HGF or Met function in the mouse results in defective delamination and migration of these muscle progenitors from the dermomyotome and, therefore, they are absent from their target regions Maina et al, 1996;Dietrich et al, 1999). Previous work using zebrafish has also demonstrated that Met signaling is required for muscle progenitor cell migration from the somites to form fin hypaxial muscle (Haines et al, 2004).…”
Section: Introductionmentioning
confidence: 99%